LsMYB15 Regulates Bolting in Leaf Lettuce (Lactuca sativa L.) Under High-Temperature Stress - Chen, Li; Xu, Mengnan; Liu, Chaojie; Hao, Jinghong; Fan, Shuangxi; Han, Yingyan (Frontiers in Plant Science, 2022)
High temperature is one of the primary environmental stress factors affecting the bolting of leaf lettuce. To determine the potential role of melatonin in regulating high-temperature-induced bolting in leaf lettuce (Lactuca sativa L.), we conducted melatonin treatment of the bolting-sensitive cultivar “S39.” The results showed that 100 μmol L−1 melatonin treatment significantly promoted growth, and melatonin treatment delayed high-temperature-induced bolting in lettuce. RNA-seq analysis revealed that the differentially expressed genes (DEGs) involved in “plant hormone signal transduction” and “phenylpropanoid biosynthesis” were significantly enriched during high-temperature and melatonin treatment. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) analysis suggested that the expression patterns of abscisic acid (ABA)-related genes positively correlated with stem length during leaf lettuce development. Furthermore, weighted gene co-expression network analysis (WGCNA) demonstrated that MYB15 may play an important role in melatonin-induced resistance to high temperatures. Silencing the LsMYB15 gene in leaf lettuce resulted in early bolting, and exogenous melatonin delayed early bolting in leaf lettuce at high temperatures. Our study provides valuable data for future studies of leaf lettuce quality.